Traditional Chian-Cui Games as a Manifestation of Local Cultural Tourism for the Meranti Islands Community - Dedi Nofrizal; Hari Setijono; Heny Setyawati; Nasuka Nasuka; Erna Lestari Rambe (International Conference on Science, Education, and Technology, 2021)
Indonesia is a large country with islands stretching from Sabang to Merauke, making Indonesia the largest archipelagic country globally. As a sizeable multicultural country, there are various kinds of culture and traditional games in it. One of them is the conventional Chian-Cui game. Chian-Cui is one of the conventional games typical of the Meranti Islands Long Strait, where this game is a water war game that involves many creations and people. Chian-Cui is a water war game often played during Chinese New Year celebrations for the Selatpanjang Chinese community. This article aims to reveal and introduce traditional games typical of the Meranti Islands. The method used in this study is a qualitative approach, where the data obtained in the field are then documented and described in the form of a qualitative descriptive narrative. The results obtained in this study include the traditional game of Chian-Cui Selatpanjang Meranti Islands can add to the atmosphere of excitement and entertainment for the community in celebrating the Chinese New Year. Furthermore, the conventional Chian-Cui game can increase local and foreign tourists every year. When entering the Chinese New Year celebration, many local and foreign tourists visit Selatpanjang. Furthermore, the traditional game of Chian-Cui Selatpanjang Meranti Islands can be a manifestation of the introduction of the local culture of the Selatpanjang community, especially the Chinese community and the Meranti Archipelago Malay community.